Simultaneous Measurement of Axial Strain and Temperature Based on a Z-Shape Fiber Structure - Chi Zhang; Ping Lu; Hao Liao; Wenjun Ni; Xin Fu; Xinyue Jiang; Deming Liu; Jiangshan Zhang (IEEE Photonics Journal)
A Z-shape fiber structure fabricated by CO2 laser is proposed here for the simultaneous measurement of axial strain and temperature. The Z-shape structure is fabricated by simply exposing a single mode fiber (SMF) to the focused CO2 laser that causes the unbalanced residual stress relaxation between the upper surface and lower surface of the fiber. The laser irradiation also gives rise to efficient coupling between the core mode and cladding modes. Then, a Mach–Zehnder interferometer is prepared. Experiments and theoretical analyses have been carried out to verify the feasibility of applying the proposed structure to simultaneous strain and temperature measurement. Experimental results indicate that the sensitivities of strain and temperature obtained by the two resonant dips are 129.78 pm/με, 43.57 pm/°C, and 51.05 pm/με, 62.1 pm/°C, respectively. Thanks to its highly sensitive spectral response, the proposed sensor will have attractive potential applications in dual parameter fiber sensing.